The Role of Strategic Alliances in Complementing firm Capabilities - Rice, J.; Liao, T.; Martin, N.; Galvin, Peter (eContent Management Pty Ltd, 2012)
Abstract: Strategic alliance research emerged to explain alliance formation based upon transaction cost minimisationand opportunism reduction. Later research, and early research from Japan, emphasised the role of alliances in facilitatingthe transfer of knowledge between organisations. Most recently, alliance research has focussed on the development of shared,potentially idiosyncratic, resource stocks. This paper builds on this recent research, testing the proposition that alliances areimportant vehicles allowing firms to access or acquire external resources, hence shoring up capability gaps and buildingnew capabilities as required during firm, product and industry life cycles. Using a sample from Australian manufacturingsmall-and-medium-sized enterprises, the paper reveals that alliances employed by firms can be viewed as initiatives toeither fill a gap in the firm’s resource stock or to exploit a perceived opportunity in its operational and strategic environment.